Utar Vehicles Tracking App - Wong, Jia Ying (2021)
UTAR provides transport services for students and staffs to allow them to go to the university for classes or work and other places more conveniently. However, there are several problems in existing transport services such as lack of real time information to enable students and staffs to have better knowledge on current transport services and ease of getting the latest routes and schedules information. Hence, this project aimed to provide a platform for students and staffs to track UTAR vehicles on real time and obtain routes and schedules information more conveniently. Other than that, this project sought to provide a platform for UTAR transport section to manage transport services more efficiently and effectively. The project objective is to develop a vehicle tracking application for UTAR students and staffs and UTAR transport section. The development methodology adopted in this project was evolutionary prototyping methodology. The final outcome of this project is 3 applications, which are the driver’s mobile application for sending location updates, the students and staffs’ mobile application and the transport section administrative staff’s web application. At the end of this project, the project objectives planned were achieved and all 3 applications were successfully developed.